In vitro propagation of Carica papaya L. cv. eksotika via somatic embryogenesis / Baker Mohammad Hussein al-Shara - Baker Mohammad, Hussein al-Shara (2018)
This thesis summarizes the optimal protocols to achieve in vitro micropropagation of Carica papaya ‘Eksotika’ using somatic embryogenesis. Half strength MS medium supplemented with 10 mg L-1 Dichlorophenoxyacetic acid (2,4-D) and 18 mg L-1 of boric acid produced high yields of somatic embryos. ½ MS medium augmented with 10 mg L- 1 phloroglucinol was found to be best suited for embryo maturation. The well-formed embryos produced shoots in MS medium supplemented with 0.05% activated charcoal, elongated in MS medium supplemented with 1 mg L-1 gibberellic acid (GA3), 0.5 mg L-1 indol-3- acetic acid (IBA), 100 mg L-1 Myo-insitol and 3.76 mg L-1 riboflavin and produced roots in MS medium after being cultured for four days in full strength MS medium supplemented with 2 mg L-1 IBA. After the rooting phase, in vitro plantlets were acclimatized in peatmos soil. For artificial seeds, the somatic embryos encapsulated in MS medium without calcium demonstrated the highest percentage of shoot formation and the lowest percentage of callus formation at the base end of somatic embryos. Histological analysis demonstrated that somatic embryogenesis could be induced from embryogenic cells that originated in meristematic centers or from clusters of cells. The pro-embryos, globular-shaped embryos, heart-shaped embryos, torpedo-shaped embryos and cotyledonary stages were found to closely resemble the ontogeny of zygotic embryos. Active gene expression of all selected genes, namely CpLAX2, CpLAX3 and CpPIN4, were detected in all somatic embryos collected during the maturation and germination phases. All genes (CpLAX2, CpLAX3 and CpPIN4) were involved in the development and growth of somatic embryos.